Marker-Assisted Improvement of the Elite Maintainer Line of Rice, IR 58025B for Wide Compatibility (S5n) Gene - Priyadarshi, Rahul; Arremsetty, Hari P. S.; Singh, Akhilesh K.; Khandekar, Durga; Ulaganathan, Kandasamy; Shenoy, Vinay; Sinha, Pallavi; Singh, Vikas K. (Frontiers in Plant Science, 2018)
The degree of heterosis in different hybrid rice varieties is reported to be at the highest in indica/japonica cross combination, however, there is a problem of sterility and semi-sterility in such inter sub specific hybrids. To overcome this problem, it is essential to develop parental lines having wide compatibility (S5n) gene. In this study, a functional marker S5-InDel was used for marker-assisted backcrossing (MABB) to introgress S5n gene from Dular into the genetic background of a widely grown recurrent parent IR 58025B, a maintainer line of wild-abortive (WA) cytoplasmic male sterile line, IR 58025A. Further, a closely linked marker nksbadh2 was used for the identification of plants devoid of aroma in backcross population to develop hybrids with no aroma. The stringent phenotypic selection followed by background selection of BC3F4 identified plants with 94.50% to 96.70% of the recurrent parent genome recovery of lines carrying S5n gene. Subsequently, at ten promising BC3F5 lines possessing S5n gene with high yielding and long-slender grain type were validated for their maintainer behavior through test crosses with IR 58025A. Also the improved lines showed significantly improved spikelet fertility performance while crossed with japonica and javanica testers in comparison to the original recurrent parent. The improved lines developed in the present study, are being converted to CMS lines through marker-assisted backcross breeding to facilitate precise and improved hybrid breeding program in rice.